A Call for the Development of a Sustainable Pest Management Program for the Economically Important Pest Flies of Livestock: a Beef Cattle Perspective. Issue 1 (4th May 2022) - Smith, K V; DeLong, K L; Boyer, C N; Thompson, J M; Lenhart, S M; Strickland, W C; Burgess, E R; Tian, Y; Talley, J; Machtinger, E T; Trout Fryxell, R T
Abstract: Filth fly pests have a substantial impact on livestock production; annual losses from filth flies were estimated at over US$1.5 billion in 1981. Knowing filth fly management and animal production have changed significantly over the past 40 yr, our objective is to lay the foundation for the development of a transdisciplinary integrated pest management (IPM) approach that considers the economics of controlling flies in animal production, with most of the examples provided towards beef cattle production systems. By performing an in-depth literature review, it is our goal to highlight losses and expenditures associated with the damages caused by these flies, discuss current management strategies for the system, and propose industry needs in terms of research gaps and producer education to enhance sustainable livestock production. Immediate industry needs include: (1) developing dynamic economic thresholds incorporating animal welfare, economics, impacts of chemical use, and climate-related responses; (2) improving monitoring methods to improve surveillance efforts for flies as a system and how all types collectively shape the system; and (3) updating economic loss assessments to account for losses due to animal defensive behaviors, reduced feed efficiency, and unplanned expenditures. While we focus on the beef cattle system in the United States, this paper is meant to provide an argument for research in worldwide livestock production (e.g., dairy, poultry, swine, and small ruminant).